The Brazilian voter : mass politics in democratic transition, 1974-1986 - Mettenheim, Kurt von, 1957- (Pitt Latin American series., 1995)
"Uses survey data from 1974, 1978, and 1982 elections. Analyzes voting and public opinion during the transition. Argues that voting studies need to be more open to national differences: Brazilian voters are less driven by ideology than by plebiscitarian appeals and patronage-based machines"--Handbook of Latin American Studies, v. 57.